A systematic mapping study on participatory game design with children - Galvão, Ludmilla; García, Laura Sánchez; Felipe, Tanya Amara (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Games can be effective tools for the processes of teaching and learning since they can engage students and increase their chances of understanding concepts and developing skills. However, the game design process has been mostly limited to professionals, often resulting in games that may not align with children's interests. Involving children in the design process allows them to express their interests and values and exercise skills like decision-making and organization. A Systematic Mapping Study (SMS) was conducted to explore research on the design and specification of games involving the participation of children. The SMS served as the basis of the development of a methodology for designing educational games for deaf children, involving game developers, teachers, and the children themselves. The SMS provided insights into game design sessions, including their structure, duration, and activities. The review also offered recommendations on conducting such sessions and highlighted the benefits and challenges associated with involving children in game design.